MAINTAINING HEALTH THROUGH EXTRACURRICULAR LEISURE EXERCISING - Ileana-Monica POPOVICI; Lucian POPESCU; Cristina-Elena MORARU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
In an increasingly aggressive environment, physical activity and physical condition play a positive role in maintaining the physical and mental health of children, in the context of preventive medicine. They influence the health status during these periods and the adulthood. The purpose of this paper is to pinpoint directions through which we can demonstrate the effectiveness of using - within extracurricular activities - certain selected physical exercises, for maintaining the health of middle school children, by studying the evolution of the group included in the study. The subjects comprised in our investigation are students aged between 12 and 14; we have conducted several somatic and functional measurements: thoracic elasticity, vital capacity, Adrian Ionescu index, and Bouchard, Demeny, and Ruffier tests. We have monitored our study sample throughout an academic year and we have introduced various sets of well-balanced physical development and handball lessons within extracurricular activities (we had practice three times a week). Through the means and methods used in extracurricular activities, the subjects scored higher values of lung elasticity (from 7.65 cm to 9.7 cm), in vital capacity (from 2430 cm³ to 2595 cm³); they improved the Ruffier index (by -3.27) and the mean value of the Bouchard test (from 316.94 g to 319.73 g). In the Demeny test, the mean increased from 50.86 cm³ to 52.22 cm³, but these values range within satisfactory parameters, while the values of Adrian Ionescu index increased from 5.75 to 7.5, which proves that students have good proportions and they range within normal development parameters. We posit that we have attained our purpose and that this study is an effective working instrument for physical education teachers who want to introduce extracurricular activities, for both influencing the growth and development process and maintaining the health of middle school students.